THE AI FIX REFLECTIONS ON THE USE AND ABUSE OF TECHNOLOGY - Richard Goodall (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article addresses the ubiquitous influence AI has on all of our lives at the moment — the fix we are in. With our smart phones informing us of our addictive tendency — “Your screen time was up 10% last week - over 6 hours 42 minutes a day!” — our fixation with ‘the machine’ (entertainment … ‘edutainment’ too) is turning us into passive consumers. Marshall McLuhan argues that the use of the medium itself is the message to be understood and this essay presents one direction we, as academics at least, may perhaps take to fix the problem which is stealing our humanity and draining our Ko’ngil.